2022
DOI: 10.1007/s11356-022-20036-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of plant-based coagulants for turbidity and cyanobacteria blooms removal

Abstract: In recent years, the proliferation of Harmful Cyanobacterial Blooms (CyanoHABs) has increased with water eutrophication and climate change, impairing human health and the environment in relation to water supply. In drinking water treatment plants (DWTPs), the bio-coagulation based on natural coagulants has been studied as an eco-friendly alternative technology to conventional coagulants for both turbidity and CyanoHABs removal. Plant-based coagulants have demonstrated their coagulation efficiency in turbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 125 publications
0
14
0
Order By: Relevance
“…Limited information on the cost of raw natural coagulants is available (Ang & Mohammad, 2020; El Bouaidi et al, 2022). In some studies, the cost of natural coagulants has been shown to be less than that of chemical coagulants generally requiring intensive pH adjustment of the water to be treated to achieve the desired removal efficiency (Choy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited information on the cost of raw natural coagulants is available (Ang & Mohammad, 2020; El Bouaidi et al, 2022). In some studies, the cost of natural coagulants has been shown to be less than that of chemical coagulants generally requiring intensive pH adjustment of the water to be treated to achieve the desired removal efficiency (Choy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These plant species are characterized by the presence of several compounds, namely, proteins, polysaccharides, phenol and flavonoids substances, cellulose, and pectin (Madhu et al, 2020; Ouhaddou et al, 2022; Rostami‐Vartooni et al, 2016), which have been proven in the literature to exhibit a coagulant effect allowing their application to remove algal cells and organic matter (El Bouaidi et al, 2022; Graham et al, 2010; Kebaili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous existing approaches have been adopted to remove CyanoHABs and their deleterious MCs from water sources. Indeed, some technologies, like coagulation-flocculation, air floatation, sedimentation, filtration, and disinfection, show high removal efficiencies of cyanobacteria cells [8][9][10][11]. These conventional methods are, however, ineffective for removing soluble MCs released into water during cell aging and/or as a result of cell deterioration caused by external stressors or by the treatment itself [12,13].…”
Section: Introductionmentioning
confidence: 99%